2023
DOI: 10.1186/s12891-023-06805-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hip joint function and analysis of risk factors for internal fixation failure after Femoral Neck System (FNS)

Yazhong Zhang,
Xu Zhang,
Chao Li
et al.

Abstract: Objective Analysis of the risk factors affecting hip function and complications after femoral neck system (FNS) surgery for femoral neck fractures is of great significance for improving the procedure’s efficacy. Methods The data of patients with femoral neck fractures who underwent FNS surgery in our hospital between October 2019 and October 2020 were retrospectively analyzed. Age, gender, time from injury to operation, fracture classification, ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Previous research on risk factors for failure after FNS fixation has reported that displaced fracture type and reduction quality are associated with failure. 16) In our study, we also found that a displaced fracture and poor reduction quality were risk factors for early failure. Displaced fractures are more difficult to reduce and are more likely to result in poor quality of reduction.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Previous research on risk factors for failure after FNS fixation has reported that displaced fracture type and reduction quality are associated with failure. 16) In our study, we also found that a displaced fracture and poor reduction quality were risk factors for early failure. Displaced fractures are more difficult to reduce and are more likely to result in poor quality of reduction.…”
Section: Discussionsupporting
confidence: 63%
“… 29) Some studies have reported early full weight-bearing after FNS fixation, while others have reported that early ambulation before 6 weeks postoperatively is a risk factor for failure after FNS. 16 30) Our study used a sequential protocol from standing to toe-touch ambulation, gradually increasing partial weight-bearing, followed by full weight-bearing, rather than mandating full weight-bearing at a specific postoperative time point as in other studies, which may have reduced the risk of early failure of the FNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation